Biblioteca Comunitaria de Guápulo - Díaz, María José (2020)
Libraries hardly form part of Quito’s daily life. The city cultural development (individual and collective) takes place outside libraries due to their closed and rigid structure. As an alternative, people search for flexible and open spaces that allow freedom of action. This is the case of Guápulo, where the artistic, historical and cultural dynamism emerges in public spaces such as the street...